Differential Effects of IGF-1R Small Molecule Tyrosine Kinase Inhibitors BMS-754807 and OSI-906 on Human Cancer Cell Lines - Fuentes-Baile, María (Cancers (Basel), 2020)
SIMPLE SUMMARY: We have tested the effects of IGF-1R tyrosine kinase inhibitors BMS-754807 (BMS) and OSI-906 (OSI) on human colon, pancreatic carcinoma cell, and glioblastoma cell lines and primary cultures. Although OSI and BMS are able to inhibit IGF-1R activity at low doses, the differential effect on cell proliferation and cell-cycle phase distribution shown by both compounds probes that many effects observed are mediated by BMS off-target interactions. Using MAPKs ELISAs and phospho-RTK array analysis, we have identified several BMS regulated putative kinases able to mediate BMS off-target effects. Interestingly, molecular docking assays suggest that BMS could affect these kinases not only by blocking their ATP-binding domain, but also by means of allosteric interactions. Since BMS has an important antineoplastic effect on these poor prognosis types of cancer, these compounds could be taken in consideration for treatment independently of IGF-1R status. ABSTRACT: We have determined the effects of the IGF-1R tyrosine kinase inhibitors BMS-754807 (BMS) and OSI-906 (OSI) on cell proliferation and cell-cycle phase distribution in human colon, pancreatic carcinoma, and glioblastoma cell lines and primary cultures. IGF-1R signaling was blocked by BMS and OSI at equivalent doses, although both inhibitors exhibited differential antiproliferative effects. In all pancreatic carcinoma cell lines tested, BMS exerted a strong antiproliferative effect, whereas OSI had a minimal effect. Similar results were obtained on glioblastoma primary cultures, where HGUE-GB-15, -16 and -17 displayed resistance to OSI effects, whereas they were inhibited in their proliferation by BMS. Differential effects of BMS and OSI were also observed in colon carcinoma cell lines. Both inhibitors also showed different effects on cell cycle phase distribution, BMS induced G(2)/M arrest followed by cell death, while OSI induced G(1) arrest with no cell death. Both inhibitors also showed different effects on other protein kinases activities. Taken together, our results are indicative that BMS mainly acts through off-target effects exerted on other protein kinases. Given that BMS exhibits a potent antiproliferative effect, we believe that this compound could be useful for the treatment of different types of tumors independently of their IGF-1R activation status.